White emissive europium complex with CRI 95%: butterfly vs. triangle structure. Issue 34 (3rd August 2020) - Devi, Rachna; Boddula, Rajamouli; Tagare, Jairam; Kajjam, Araind Babu; Singh, Kasturi; Vaidyanathan, Sivakumar
Abstract : The spectral window of dual visible light emissions of the molecular europium complex that leads to white light can be modulated by design strategy. Abstract : The spectral window of dual visible light emissions of the molecular europium complex that leads to white light can be modulated by design strategy. A europium complex with butterfly structure displays dual emission that leads to single phase white light-emitting molecular complex with excellent colour quality. Such behaviour is not observed with an analogous europium complex with a triangular structure (rather shows usual red emission), suggesting that the partial lighting up of europium ion along with the ligand (antenna) emission (controlled energy transfer from ligand to the Eu(iii ) ion) is more imperative for the creation of white light. The white light emitting diode (LED) assembled using butterfly europium phosphor as a white emitter yields a bright pure white light with CRI (95%), CCT (5457 K), and CIE ( x = 0.33, y = 0.33), whereas the triangle Eu-phosphor displays red light with CIE value of x = 0.58, y = 0.31. The fabricated white/red LED continued to emit a bright white/red light for more than a year. The present design strategy can be widely adapted for the synthesis of single-phase white emitting Eu-phosphor. In addition, the presently studied complexes have also been explored for temperature sensing and as a sensor for vapoluminescence.